1997
DOI: 10.1080/10934529709376711
|View full text |Cite
|
Sign up to set email alerts
|

Biologically enhanced dissolution of a pyrite‐rich black shale concentrate

Abstract: The acid leaching of a pyrite-rich black shale concentrate (7% S) was tested in this study. The experiments were performed at 5-30% pulp densities and with inoculations of Fe-and S-oxidizing thiobacilli (Thiobacillus ferrooxidans and Thiobacillus thiooxidans). Cultures supplemented with S° showed strong acid production, with final pH values of 0.9 in T. ferrooxidans cultures and 0.4-0.5 in the presence of T. thiooxidans. Fe dissolution was pronounced in the T. ferrooxidans culture whereas T. thiooxidans did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…galvanic dissolutions, oxidation by O 2 e Fe 3+ ; [1]), resulting in acid generation and toxic element mobilization. This process is often mediated by the activity of iron-oxidizing bacteria and archea, such as Acidithiobacillus ferrooxidans and Leptospirillum ferrooxidans [2, 3, 4, 5], which are able to continuously oxidise Fe 2+ perpetuating pyrite oxidation [3]. Recently, Zotti et al.…”
Section: Introductionmentioning
confidence: 99%
“…galvanic dissolutions, oxidation by O 2 e Fe 3+ ; [1]), resulting in acid generation and toxic element mobilization. This process is often mediated by the activity of iron-oxidizing bacteria and archea, such as Acidithiobacillus ferrooxidans and Leptospirillum ferrooxidans [2, 3, 4, 5], which are able to continuously oxidise Fe 2+ perpetuating pyrite oxidation [3]. Recently, Zotti et al.…”
Section: Introductionmentioning
confidence: 99%
“…The association of aerobic, acidotolerant/acidophilic iron oxidizers with acidic environments in this study (Figure 4) is unsurprising, as the bioenergetic favourability of aerobic microbial iron oxidation is known to be restricted below pH 4 (Hedrich et al 2011). Previous studies have shown that microbial iron oxidation in shale is predominated by the oxidation of pyrite (FeS2), in which both the iron and sulfur become oxidized (Tasa et al 1997;Joeckel et al 2005;Li et al 2014). The oxidation of pyritic sulfur to sulphuric acid lowers environmental pH, which in turn facilitates the growth of iron oxidizing microbes and the continued dissolution of pyrite (Vera et al 2013, but see also Samuels et al 2019).…”
Section: Discussionmentioning
confidence: 59%
“…Furthermore, microbial rock weathering activity has been indicated to increase environmental pollution from mining wastes (Wengel et al 2006;Kalinowski et al 2006) and to contribute to rock expansion in shale bedrock, causing significant damage to infrastructure (Anderson, 2008;Hoover and Lehmann, 2009). Such application-focused studies often quantify the biologically enhanced rate of elemental leaching from rock as a measure of the weathering potential of individual microbial strains (Tasa et al 1997;Anjum et al 2010) or microbial communities (Lee et al 2005;Matlakowska et al 2012;Włodarczyk et al 2015). These studies have revealed numerous microbial rock weathering mechanisms including the oxidation of iron (Tasa et al 1997, Grobelski et al 2007Spoalore et al 2011) secretion of siderophores (Kalinowski et al 2006, Włodarczyk et al 2015) and organic acid production (Anjum et al 2010;Włodarczyk et al 2016) that result in the enhanced dissolution and degradation of shale.…”
Section: Introductionmentioning
confidence: 99%
“…In the first step, bacteria get attached to pyrite surface and initiate the solubilization of pyrite to ferrous sulphate. It was recently observed that fraction solubilized from solid phase is responsible for toxicity of black-shale leachate [28]. This causes a decline in redox potential of the leachate.…”
Section: Discussionmentioning
confidence: 99%